Understandings of reproductive tract infections in a peri-urban pueblo joven in Lima, Peru - Parker Kea; Winch Peter J; Hernández Lisa; Gilman Robert H (BMC, 2006)
Abstract Background Control programs for Reproductive Tract Infections (RTIs) typically focus on increasing awareness of risks associated with different forms of sexual contact, and pay little attention to how or why people may link RTIs to other features of their physical or social environments. This paper describes how women in a peri-urban pueblo joven located in the coastal desert surrounding Lima, Peru conceptualize the links between RTIs, sexual behaviour, personal hygiene, and the adverse environment in which they live. Methods We combined qualitative interviews and a participatory voting exercise to examine social and physical environmental influences on RTIs and gynaecologic symptom interpretation. Results Knowledge of RTIs in general was limited, although knowledge of AIDS was higher. Perceived causes of RTIs fell into three categories: sexual contact with infected persons, personal hygiene and exposure to the contaminated physical environment, with AIDS clearly related to sexual contact. The adverse environment is thought to be a major contributor to vaginal discharge, "inflamed ovaries" and urinary tract infection. The more remote parts of this periurban squatter settlement, characterized by blowing sand and dust and limited access to clean water, are thought to exhibit higher rates of RTIs as a direct result of the adverse environment found there. Stigma associated with RTIs often keeps women from seeking care or obtaining information about gynaecologic symptoms, and favours explanations that avoid mention of sexual practices. Conclusion The discrepancy between demonstrated disease risk factors and personal explanations influenced by local environmental conditions and RTI-related stigma poses a challenge for prevention programs. Effective interventions need to take local understandings of RTIs into account as they engage in dialogue with communities about prevention and treatment of RTIs.